Future States for Hearing Care - Windmill, Ian M. (Seminars in Hearing, 2022)
Evolutionary changes occur across health care, including within the hearing care delivery system. At times, the change is driven by external forces and thus elicits a reactive response. In contrast, developing a vision of a future state, and subsequently the strategies to achieve that vision, is a proactive and a preferred process. Using the reactive versus proactive framework, a future state built around the emergence of genetics as both an assessment tool and a treatment option is presented. In addition, a broad, consumer-centric vision for access to affordable and contemporary hearing care is presented that would result in an expanded and positive future state for hearing care services.
Keywords: future state; hearing care; stakeholders; health policy; genetics